792 Sleep and Daytime Function in Patients with Multiple Sclerosis. (3rd May 2021) - Aljundi, Nawar; Arvai, Kelsey; Mitchell, Michael; Pandya, Nishtha; Zeineddine, Salam; Salloum, Anan; Sankari, Abdulghani; Martin, Jennifer; Badr, Safwan
Abstract: Introduction: Fatigue is a core symptom of Multiple Sclerosis (MS) and impairs function and quality of life. Studies show that sleep-disordered breathing (SDB) is also common in persons with MS and may exacerbate fatigue. Within a larger study of patients with spinal cord injuries and disorders, we evaluated the relationships among sleep-disordered breathing severity, sleep quality, and functional outcomes in patients with MS. Our objective was to examine the impact of SDB severity and sleep quality on the severity of fatigue and functional impairment in this population. Methods: Twenty-five subjects (average age=57(11), min=35, max=79; 80% male; average AHI=27(20) min=3, max=70; and 67% with AHI > 15) 24 completed in-laboratory polysomnography (PSG) to measure apnea-hypopnea index (AHI) and sleep efficiency (SE) and questionnaires about sleep and function: Insomnia Severity Index (ISI), Pittsburg Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Flinders Fatigue Scale (FFS), PHQ-9 depression scale (excluding sleep item), Brief Pain Inventory (BPI) and World Health Organization Quality of Life (WHOQOL). Relationships between sleep measures (AHI and SE from PSG, ISI and PSQI) and daytime function (ESS, FFS, PHQ-9, BPI and WHOQOL) were assessed by bivariate correlation. Results: At the baseline visit, we assessed participant's daytime sleepiness, fatigue, sleep quality, and depression. The mean scores on questionnaires: ESS was 8.0(5.6), ISI was 11.5(6.7), PSQI was 9.3(4.4), FFS was 17.3(8.7), BPI severity was 3.4 (3.13), BPI interference was 3.5 (3.5), PHQ-9 was 7.3(5.8). There were significant relationships between ISI and FFS (r=0.78, p<0.001), PSQI and FFS (r=0.68, p=0.001), ISI and WHOQOL Physical Domain (r=-0.64 p=0.001), as well as SE and FFS (r=-0.45, p=0.041). There was no significant correlation between AHI and FFS (p=0.395). Conclusion: In veterans with MS, insomnia symptom severity was associated with daytime fatigue and decreased quality of life (QOL). Insomnia may represent a modifiable cause of daytime fatigue in patients with MS. Recognition and management of insomnia may improve outcomes in this population. Further research should evaluate whether insomnia interventions may benefit daytime fatigue and improve QOL. Support (if any): VA Rehabilitation Research and Development Service, (RX002116; PI Badr); VA HSR&D RCS20-191 and NIH/NHLBI K24 HL143055 (PI Martin).